Picture Word Inductive Model (PWIM) On Writing: Patterning Words Into Sentence - Putri Novitasari; Siti Nafi’yah (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2026)
The main focus of this study was to find out whether there was significant corelation or impact of picture word inductive model (PWIM) on students’s writing  comprehension. The picture word inductive model (PWIM) was one of teaching strategy to teach students sentence structure and content simultaneously. By, using this teaching strategy researchers willing to bring an impact on students’ written communication in case of producing meaningful sentence. By this research, researchesr aplied PWIM  to boost students’ comprehension in writing descriptive sentence of certain place. Quantitative research was implemented as the research design. The sample was students of eleventh grade which contained of  41 students. They were given pre-test and post-test. The impact of PWIM can be seen from the mean scorte of the students. The mean score before given treatment by implementing PWIM was 68. 41. Meanwhile, the mean score after given treatment was 93.04. In addition, the increasing of mean score proved that there was improvement on students’ writing comprehension in producing sentence by applying picture word inductive model (PWIM) for teaching and learning proccess.